Henry Cowell’s Three Irish Legends for Piano: Interpretation and Playing Technique - Wongsaengchan, Thisara; Chulapan, Panjai (Rangsit Music Journal, 2021)
This research article focuses on Three Irish Legends for Piano composed by Henry Cowell, an American composer. The set consists 3 compositions: The Tides of Manaunaun, The Hero Sun, and The Voice of Lir. An unconventional technique called tone clusters has been applied by the composer, indicating a pianist to use forearms or the flat of the hands. To come up with precise notation of the new technique, Cowell developed new symbols as well as detailed explanations and performance instructions.